2023
DOI: 10.1111/1365-2656.13932
|View full text |Cite
|
Sign up to set email alerts
|

DeepWild: Application of the pose estimation tool DeepLabCut for behaviour tracking in wild chimpanzees and bonobos

Charlotte Wiltshire,
James Lewis‐Cheetham,
Viola Komedová
et al.

Abstract: Studying animal behaviour allows us to understand how different species and individuals navigate their physical and social worlds. Video coding of behaviour is considered a gold standard: allowing researchers to extract rich nuanced behavioural datasets, validate their reliability, and for research to be replicated. However, in practice, videos are only useful if data can be efficiently extracted. Manually locating relevant footage in 10,000 s of hours is extremely time‐consuming, as is the manual coding of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…Bat flight represents a particularly difficult challenge for deep learning networks compared to most animal movements for which the method has been used 12–18 . During flight, bats can be filmed from all directions in both the horizontal and vertical planes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bat flight represents a particularly difficult challenge for deep learning networks compared to most animal movements for which the method has been used 12–18 . During flight, bats can be filmed from all directions in both the horizontal and vertical planes.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI)–based methods for measuring animal behavior, including locomotor movement, have recently made great strides. For example, the widely used Python package DeepLabCut (DLC) 11 has been successfully applied to humans, 12 rats, 13 cheetahs, 14 macaques, 15 chimpanzees, 16 spiders, 17 and more 18 . In contrast, DLC has not been widely applied to animals in flight 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Wiltshire et al used DLC to make pose estimates of chimpanzees and bonobos. They found that the machine learning models produced pose estimations with a consistency similar or better than many different human labeling (Wiltshire et al, 2023), and in a fraction of the time required for human labeling. The model was also able to work in a variety of environments, from open clearings to dense forest.…”
Section: Introductionmentioning
confidence: 99%
“…Animal skeletal pose tracking from video data has undergone nothing short of a revolution through developments in computer vision and deep learning [1][2][3][4][5][6]. There are now many pretrained pose detection models for humans, and there are increasingly more pre-trained models for non-human animals (e.g., rhesus macaques, Macaca mulatta, [7], chimpanzees, Pan troglodytes [8,9]). These developments are key for animal research as they allow non-invasive monitoring based on video alone, which can further be used for automatic classification of behavioral patterns [10][11][12].…”
Section: Introductionmentioning
confidence: 99%